Development of Science Learning Modules with Computer-Based Test (CBT) Assessments to Train Critical Thinking Skills of Students at SMP Negeri 7 Bontang - Hendita Dyah Ratnady; Makrina Tindangen; Elsje Theodora Maasawet; Abdul Hakim; Daniel; Herliani; Yusak Hudiyono; Aloysius Hardoko (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to improve Modules for science subject with the Computer-Based Test Assessment in order to train students’ critical thinking on one of science topics which is human’s respiratory system using ADDIE model. This model of research is the development research level 3. The data were collected by involving expert’s validation, observation, test, and questionnaire. The results showed that: the module validity result in terms of module itself was 93.75% with a very valid category. The validity in terms of language and material were 88.77% and 99.54% respectively, while the results by the Computer-Based Test application were 97%. The module’s practical results assessed by questionnaires were 89.41% and it means this module is highly practical to be used. The results of the module’s efficacy in terms of normality, the n-gain of all classes in pre-test and post-test’s sig value > 0.05, therefore the data was distributed normally. The results of paired sample t-test indicate that there is a noticeable difference on the average of pre-test and post-test results in the experimental group. Hence, the science module with Computer-Based Test is effective to be utilized as learning materials that can increase students’ critical thinking skills at schools.